OFDM comparison with FFT and DWT processing for DVB-T2 wireless channels (2018)
Introduction: Recent studies on the FFT processing (Fast Fourier Transform) or DWT (Discrete Wavelet Transform) of the OFDM signal (Orthogonal Frequency Division Multiplexing) have shown pros and cons for DVB-T2 (Digital Video Broadcasting-Second Generation Terrestrial) radio communications; however, the benefits of both types of processing have yet to be compared for the same scenario. Objective− The objective of this research is to compare the response of the wireless channel with AWGN noise (Additive White Gaussian Noise Channel) and Rayleigh and Rician fading in the UHF (Ultra High Frequency) band. Methodology: The transmission of DVB-T2 information with OFDM modulation and FFT and DWT processing was simulated in Matlab®, specifically in Simulink. Results: The results of the study proved to be more ef-ficient for DWT system than FFT system, due to the low rate of erroneous bits, spectral efficiency and reduction of the Peak-to-Average Power Ratio (PAPR), for Eb / No relations greater than 10dB. Conclusions: In this article, we present the designs of both systems and the results of the research experience; likewise, the practical applicability of these systems is discussed, and improvements are suggested for future work